HISTORY OF MAHALLAS OF UZBEKISTAN AND THEIR EVOLUTION DURING THE HISTORICAL PERIOD (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
The territory of Uzbekistan is a center of ancient civilizations in cultural, economic, and social terms. The main organizing link of society here is the mahalla institution, which is closely connected with the lifestyle, customs, and social relations of the people. The mahalla institute has been formed and developed in Central Asia, including Uzbekistan, for many centuries. This article highlights the history of the emergence and development of the mahalla institute, its socio-historical significance from a long historical perspective.